An Analysis Of Language Style By The Characters In “Wonder” A Novel By R.J. Palacio - Wahyudiantari, Ni Wayan Prami (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Language style is defined as the choice of words used by a specific group of people when speak in a place and in one condition. It is very important for people to express their ideas, people use style depend on with whom they speak and where they speaking too. This research is aimed to analyze language style used by the characters in “Wonder” a novel by R.J. Palacio. The analysis was based on the five language styles proposed in Martin Joos’s theory. The research was conducted through a qualitative descriptive method. Qualitative descriptive method was used in analyzing the data because it will be explained with words, phrases, and sentences. The researcher used qualitative method in which the data was collected by reading the novel then finding out the utterances that contains language style. The data in this research were taken from the utterances of the novel. The researcher only focuses on conversation containing those five types of language style. Later on, the researcher classified them based on the types of language style that were found on the movie. The finding of this researcher is the researcher found there are five types of language style that is used by the main character, the five type of language style are Frozen Style (Oratorical Style), Formal Style (Deliberative Style), Consultative Style, Casual Style and Intimate Style.